2007
DOI: 10.1158/1541-7786.mcr-07-0055
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Molecular Signatures as Determined by SAGE: Correlation with Lymph Node Status

Abstract: Global gene expression measured by DNA microarray platforms have been extensively used to classify breast carcinomas correlating with clinical characteristics, including outcome. We generated a breast cancer Serial Analysis of Gene Expression (SAGE) high-resolution database of f2.7 million tags to perform unsupervised statistical analyses to obtain the molecular classification of breast-invasive ductal carcinomas in correlation with clinicopathologic features. Unsupervised statistical analysis by means of a ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
76
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 52 publications
10
76
1
3
Order By: Relevance
“…Kavanaugh et al (21) demonstrated that overexpression of DEK induces human keratinocyte transformation and that DEK-knockout mice are partially resistant to chemically induced papilloma formation. Previous studies have revealed that DEK mRNA expression is increased in invasive ductal breast cancer, and has an increased gene expression in high-grade and late-stage breast cancer, therefore implicating it as a potential novel target in recurrent tumors (5,(22)(23)(24). In addition, Shibata et al (25) identified that DEK overexpression affects the activity of global transcriptional regulators and is associated with tumor development and a poor prognosis of patients with high-grade neuroendocrine carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Kavanaugh et al (21) demonstrated that overexpression of DEK induces human keratinocyte transformation and that DEK-knockout mice are partially resistant to chemically induced papilloma formation. Previous studies have revealed that DEK mRNA expression is increased in invasive ductal breast cancer, and has an increased gene expression in high-grade and late-stage breast cancer, therefore implicating it as a potential novel target in recurrent tumors (5,(22)(23)(24). In addition, Shibata et al (25) identified that DEK overexpression affects the activity of global transcriptional regulators and is associated with tumor development and a poor prognosis of patients with high-grade neuroendocrine carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The age of those in the ERBB2-positive group was not significantly different from the other 2 groups. The median age of the control group was significantly younger when compared with the other groups (30.5 years [range, [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]). Two patients were lost during follow-up, and the remaining patients were followed-up for 23 to 50 months after surgical excision, with an average follow-up time of 41 months.…”
Section: Resultsmentioning
confidence: 99%
“…13,[23][24][25][26][27][28][29][30][31][32] The natural history, progression, and mechanism underlying DCIS are poorly understood, although several studies have shown that the transition from DCIS to invasive disease is associated with quantitative rather than qualitative differences in gene expression. 2,14,25,33 Biological markers to predict the presence of occult invasive disease or to identify patients at higher risk of developing invasive cancer are needed so that clinicians can better tailor the management of these lesions.…”
Section: Triple Negative Er/pr Erbb2mentioning
confidence: 99%
“…Contudo, a maioria dos trabalhos de expressão gênica avalia somente o potencial prognóstico dos genes, enquanto uma quantidade reduzida analisa o poder preditivo de genes em amostras de neoplasias primárias e metástases de linfonodos em câncer de mama (BERTUCI et al, 2000;HUANG et al, 2003;ABBA et al, 2007;FENG et al, 2007;WANG et al, 2013;VALENTE et al, 2014;CHEN et al, 2017;PAULA et al, 2017). Além disso, o significado biológico do envolvimento dos linfonodos e sua utilidade na orientação da terapia adjuvante e sistêmica tem sido objeto de muitos resultados discordantes (BERTUCI et al, 2000;HUANG et al, 2003;ABBA et al, 2007).…”
Section: Discussionunclassified